Neighbor satellite load based low orbit satellite distributed routing algorithm - Mingchuan YANG; Guanchang XUE; Qingyi LI (Tongxin xuebao)
Satellites are highly flexible and maneuverable, and they are not easily affected by ground factors, which has led to the rapid development of space satellite technology.Satellite networks always have load congestion problem as the load increases, making routing algorithms a core issue in the field of satellite network research.Based on the problems of congestion mitigation, signaling overhead, and algorithm complexity, the distributed routing algorithm for local load balancing of LEO (low earth orbit) satellite networks was deeply studied.The network model was constructed based on the Iridium satellite system and a distributed routing algorithm based on the load status of neighbor satellite (DRNL) was proposed, which included such as load status update of neighbor nodes, load balancing and routing decision.It had a certain degree of portability and could adapt to other polar or near polar orbit constellation.The simulation results based on the OPNET show that the DRNL can better adapt to the heavier network loads state, alleviate satellite congestion, obtain lower delay and packet loss.